2009
DOI: 10.1051/radiopro/20095070
|View full text |Cite
|
Sign up to set email alerts
|

Root-uptake of14C derived from acetic acid by root vegetables

Abstract: Sand culture using radish (Raphanus sativus L.) and hydroponics using carrot (Daucus carota L.) were conducted to examine root-uptake of carbon and its assimilation in the form of 14 C-acetic acid. 14 C-acetic acid (1, 2-14 C, radioactivity: 74 kBq) was added to each pot. Radishes were grown under the dark conditions or the light conditions for 24 h. Carrot were grown under the light conditions after 14 C-acetic acid addition (radioactivity: 19 kBq). The 14 C radioactivity in each plant part was determined. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…But plant growth in PA was not affected by low nitrogen level. Studies have demonstrated that low-molecule organic carbon matter in the rhizosphere can be absorbed directly by plants possibly to balance the nutrient intake, and the fermentation products of lactic acid are formic acid and acetic acid, which possibly promoted the growth of plants. However, nitrogen concentration in nutrient solution was proved to have an influence on the functional components in leaves of plants, so the quality of plants in PA still needed to be evaluated …”
Section: Discussionmentioning
confidence: 99%
“…But plant growth in PA was not affected by low nitrogen level. Studies have demonstrated that low-molecule organic carbon matter in the rhizosphere can be absorbed directly by plants possibly to balance the nutrient intake, and the fermentation products of lactic acid are formic acid and acetic acid, which possibly promoted the growth of plants. However, nitrogen concentration in nutrient solution was proved to have an influence on the functional components in leaves of plants, so the quality of plants in PA still needed to be evaluated …”
Section: Discussionmentioning
confidence: 99%